2011
DOI: 10.1002/fld.2726
|View full text |Cite
|
Sign up to set email alerts
|

A wave generation toolbox for the open‐source CFD library: OpenFoam®

Abstract: SUMMARY The open‐source CFD library OpenFoam® contains a method for solving free surface Newtonian flows using the Reynolds averaged Navier–Stokes equations coupled with a volume of fluid method. In this paper, it is demonstrated how this has been extended with a generic wave generation and absorption method termed ‘wave relaxation zones’, on which a detailed account is given. The ability to use OpenFoam for the modelling of waves is demonstrated using two benchmark test cases, which show the ability to model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
570
0
25

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 853 publications
(603 citation statements)
references
References 39 publications
8
570
0
25
Order By: Relevance
“…This unphysical wave damping caused by RANS turbulence modelling is not only observed during CFD simulations of monopiles. Several other authors also reported wave damping when using CFD for wave modelling: Mayer and Madsen (2000), Jacobsen et al (2012), Vanneste and Troch (2015) and Elhanafi et al (n.d.).…”
Section: Introductionmentioning
confidence: 93%
“…This unphysical wave damping caused by RANS turbulence modelling is not only observed during CFD simulations of monopiles. Several other authors also reported wave damping when using CFD for wave modelling: Mayer and Madsen (2000), Jacobsen et al (2012), Vanneste and Troch (2015) and Elhanafi et al (n.d.).…”
Section: Introductionmentioning
confidence: 93%
“…OpenFOAM has been used to simulate coastal processes (Jacobsen et al 2012) (Higuera et al 2013), WEC operation (Palm et al 2013) (Schmitt et al 2012), (Iturrioz et al 2013) and extreme events (Vyzikas et al 2013). It has been used in NWT applications for hydrodynamic parameter identication (Bonfiglio et al 2011) (Armesto et al 2014).…”
Section: Openfoammentioning
confidence: 99%
“…Also, removing reflection at outlet boundaries via a boundary condition works well only when the wave-length and speed of propagation is known. For those reasons, a relaxation zone approach is preferred [25], where the CFD solution is blended with the prescribed "far field" wave state within a relaxation zone.…”
Section: Waves and Relaxation Zonesmentioning
confidence: 99%